Determinan Hak Amil Pada BAZNAS Kota Makassar Periode 2019-2023 - Nur Hadiyatul Husna; Nurfiah Anwar; Trisno Wardy Putra (Al-Musthofa: Journal of Sharia Economics, 2026)
This study aims to analyze the factors that influence the amount of amil rights at the National Zakat Agency (BAZNAS) of Makassar City during the 2019–2023 period. This study uses a quantitative approach with multiple linear regression analysis methods. The data used are secondary data from the monthly financial reports of BAZNAS Makassar City. The data analysis techniques used are descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, determination tests (R2), and hypothesis testing using SPSS 23 software. The results of the study indicate that partially, the variables of zakat collection, infaq/alms distribution, and operational costs have a significant positive effect on amil rights. The zakat distribution variable has a significant negative effect on amil rights and the infaq/alms collection variable has no effect on amil rights. While simultaneously, the five variables have a significant effect on amil rights.